A dime for your time: Distribution of earnings in the Malaysian manufacturing sector - Soon, Jan Jan (2015)
This paper examines changes in the distributions of earnings of employees in the Malaysian manufacturing sector, using the Malaysian Einployee Survey data fi-om the World Bank with a sample size of slightly more than 10,000 respondents.Conventional OLS estimations answer questions such as 'Does years of education affect salary?' Quantile estimations however, address questions such as 'does years of education affect salary differently for those at the upper end of the salary distribution (the relative winners) than for those at its lower end (the relative losers) and the middle-income workers (the averages)?', where the effects of years of education on a particular earning quantile (or group) can be compared to those on other salary quantiles.Heterogeneity across different salary quantiles can therefore be studied.